RECONSTRUCTING DEMOCRATIC MEDIA GOVERNANCE AMID PLATFORM DOMINANCE IN INDONESIA - Tajudin Tajudin; Geofani Milthree Saragih; Ade Sathya Sanathana Ishwara; H. Muhamad Rezky Pahlawan MP; Fadhli Muhaimin Ishaq (Indonesia Media Law Review, 2026)
Digital platforms have become dominant actors in shaping public discourse, political communication, and democratic participation in Indonesia. While these platforms facilitate freedom of expression and access to information, their algorithmic governance also raises concerns regarding transparency, accountability, misinformation, and democratic integrity. This study aims to analyze the challenges of democratic media governance amid platform dominance and to formulate a legal reconstruction model that balances freedom of expression with algorithmic regulation. This research employs a normative juridical method using statutory, conceptual, and comparative approaches. Legal materials were collected through library research, including legislation, legal doctrines, academic journals, and relevant international regulatory frameworks, and were analyzed qualitatively using descriptive-analytical methods. The findings demonstrate that Indonesia’s existing media regulatory framework remains inadequate in addressing the legal consequences of algorithmic control exercised by digital platforms. The absence of comprehensive standards concerning transparency, accountability, and public oversight has weakened democratic governance within the digital public sphere. This study concludes that democratic media governance in Indonesia requires a reconstructed legal framework that strengthens platform accountability, promotes algorithmic transparency, protects freedom of expression, and ensures democratic oversight in the digital era.